An extension theorem from connected sets and homogenization of non-local functionals. (July 2021) - Braides, Andrea; Chiadò Piat, Valeria; D'Elia, Lorenza
Abstract: We study the asymptotic behaviour of convolution-type functionals defined on general periodic domains by proving an extension theorem.